2021
DOI: 10.1088/1742-6596/1964/4/042022
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Network for Rainfall Analysis Using Deep Learning Techniques

Abstract: The estimation of rainfall is one of the most critical and daunting challenges in today’s environment. Weather and rainfall are typically extremely nonlinear and dynamic, needing sophisticated machine models and simulation for forecasting accurately. The economy of India is agriculture and is focused primarily on crop production and precipitation. Predictions of rainfall are important for all farmers to assess crop productivity. Rainfall forecast involves the application of science and technology to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…and self-treatment. Network output varies depending on network connectivity, load speed and operating pressure [3][4][5]. The network itself can be either an algorithm or a function included in a given context and can be an indicator of a good idea.…”
Section: Literature Reviewmentioning
confidence: 99%
“…and self-treatment. Network output varies depending on network connectivity, load speed and operating pressure [3][4][5]. The network itself can be either an algorithm or a function included in a given context and can be an indicator of a good idea.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Following studies by [52,53,59], which used water vapor in the atmosphere and soil moisture as ancillary variables, this study merged two models based on an MLR framework, as defined below:…”
Section: Multivariant Linear Regression Modelmentioning
confidence: 99%
“…Some of these studies have evaluated IMERG data on a global scale (e.g., [6]), while others have focused on some specific areas of the globe such as Europe [7][8][9], vast territories throughout Asia [10][11][12][13][14][15], and America [16][17][18][19]. Their investigations suggest the promising use of IMERG to estimate Learning (ML) techniques, such as ANNs, have been increasingly applied in rainfall studies due to their ability to extract a non-linear relationship between independent and dependent variables, without the need for predefined relationships; this has led to a significant improvement compared to traditional blending methods [46,49,[52][53][54][55]. A summary of selected literature reviews in this field is reported in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…These studies concluded that many studies have used ANN in predicting future weather and also concludes that data mining techniques, especially ANN can be used to predict weather conditions accurately. [5] states that some researchers use ANN for rainfall prediction, because it is a valid and more accurate method than conventional mathematics or numerical approaches. This paper discusses the comparison of the predicted perceived value with BPN, RBFN, SVM.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because the factor of sufficient water availability will support agricultural productivity. So it is necessary to involve science and technology to determine weather conditions [5].…”
Section: Introductionmentioning
confidence: 99%